2003
DOI: 10.1177/1078087403038005004
|View full text |Cite
|
Sign up to set email alerts
|

The Desegregation Efficiency of Magnet Schools

Abstract: Magnet schools are an attempt to introduce market incentives into school desegregation policy. The analyses presented here assess the extent to which they have improved the effectiveness of desegregation plans in a 600-school-district national sample from 1968 to 1991. I find that adding magnet schools to a voluntary plan does not seem to produce any more interracial exposure than does a voluntary plan without magnets. Moreover, there are diminishing marginal returns to magnets. The greater the percentage of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 13 publications
0
18
2
Order By: Relevance
“…The original research was funded by the U.S. Department of Education from 1990 to 1993 with Christine Rossell and David Armor as co-principal investigators and Roger Levine and Lauri Steele, American Institutes for Research, as contract managers. Published works using this data file are Rossell (2003), Rossell (2002), Armor and Rossell (2002), Rossell and Armor (1996) and Steel, Levine, Rossell and Armor (1993). The sampling frame for the survey data was the set of U.S. school districts in which two or more schools offer at least one grade level (K-12) in common.…”
Section: Rossell and Armor Survey Datamentioning
confidence: 99%
“…The original research was funded by the U.S. Department of Education from 1990 to 1993 with Christine Rossell and David Armor as co-principal investigators and Roger Levine and Lauri Steele, American Institutes for Research, as contract managers. Published works using this data file are Rossell (2003), Rossell (2002), Armor and Rossell (2002), Rossell and Armor (1996) and Steel, Levine, Rossell and Armor (1993). The sampling frame for the survey data was the set of U.S. school districts in which two or more schools offer at least one grade level (K-12) in common.…”
Section: Rossell and Armor Survey Datamentioning
confidence: 99%
“…The approach was simple: draw white students to predominantly black schools in the inner city by offering well‐funded themed schools, such as performing arts or science and technology, which combined innovative learning with an integrated school. Recently, there are more than 3,000 magnet or theme‐based schools (Rossell, 2003). Magnet schools differ in how they implement their programs.…”
Section: Research Objectives and Methodologymentioning
confidence: 99%
“…Mandatory magnet programs decreased minority students' exposure to their White peers, but they promoted racial balance within these schools. In another quantitative study on desegregation and magnet school programs, Rossell (2003) also reported that school districts with voluntary magnet programs decreased interracial exposure and produced more White flight. However, school desegregation plans with majority to minority schools resulted in more interracial exposure and less White flight, but a higher number of school districts serving predominantly African American students.…”
Section: Magnet Programs In Public Schoolsmentioning
confidence: 96%